Genetic modulators of hemolytic anemia in Angolan children with sickle cell anemia - Germano, Isabel (2021)
Sickle Cell Anemia (SCA) is a recessive genetic disease caused by the c.20A>T variant in the HBB gene. It is characterized by sickled erythrocytes, chronic hemolytic anemia, and vaso-occlusive events. However, these manifestations are heterogeneous due to environmental and genetic modifying factors. The aim of this study was to investigate genetic modifiers of hemolytic anemia in pediatric SCA patients living in Africa, where the disease is a severe public health problem. The study was conducted on 200 Angolan SCA 3-12-year-old children. Thirteen polymorphic regions in genes previously associated with vascular cell adhesion (VCAM1 and CD36), vascular tonus (NOS3), or erythrocyte hemoglobinisation (HBA), were genotyped using PCR, RFLP, Gap-PCR, and Sanger sequencing. Hematological and biochemical phenotypes were obtained at a steady state and clinical adverse events were collected from the patient's medical records. Results revealed a high level (67.5%) of α-thalassemia co-inheritance (del. 3.7kb in HBA), which improves patients’ health by delaying the onset of the disease, decreasing anemia, and the number of blood transfusions. Two SNPs in CD36 (rs1984112 and rs1413661) showed an impact on anemia severity. Particularly, genotypes containing the rs1413661_allele C were revealed to be risk factors for severe anemia, as they were associated with lower hemoglobin levels, increased number of hospitalizations, and transfusions. This is the first report associating this SNP with SCA pathology. Moreover, the rs1041163_allele C in VCAM1 was associated with lower LDH levels, inversely the rs2070744_allele C in NOS3 was associated with higher LDH levels and a higher number of hospitalizations, being a possible risk factor for increased hemolytic rate. This study contributed to the understanding of SCA complex pathophysiology. It confirmed the positive role of α-thal., both in SCA-related anemia and in its clinical manifestations. In addition, it reinforced the importance of vascular cell adhesion in hemolytic anemia variability. In this context, we propose the SNP rs1413661 in CD36 as an important novel genetic modulator of SCA in Africa.